Statistical hadronization of charm in heavy-ion collisions at SPS, RHIC and LHC - Andronic, Anton; Braun-Munzinger, Peter; Stachel, Johanna (Physics letters, 2003)
We study the production of charmonia and charmed hadrons in nucleus-nucleus collisions at SPS, RHIC, and LHC energies within the framework of the statistical hadronization model. Results from this model are compared to the measured yields and centrality dependence of J/ψ production at SPS and RHIC energies. We explore and contrast the centrality dependence of the production of mesons with open and hidden charm at SPS, RHIC and LHC. The sensitivity of the results to various input parameters is analyzed in detail for RHIC energy.